Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.